A Healthy Lifestyle in the Opinion of Junior High School Students From Myślenice District (Poland) - Mazur, Piotr; Łętocha, Monika (Journal of Vasyl Stefanyk Precarpathian National University, 2016)
Diseases of the twenty-first century contribute significantly to the deterioration of the quality of human life and shorten its length. A healthy lifestyle is to ensure optimal health and minimise the risk of contemporary diseases of civilization. The aim of the article is to present the opinions on healthy lifestyle of the junior high school students from Myślenice district in Poland